Preparation and application of a mineral functional membrane coupled with advanced oxidation technology

The two-dimensional layered silicate mineral film loaded with transition metal ions/oxides, combined with advanced oxidation technology, forms a composite film, which solves the problem of low efficiency in removing difficult-to-degrade pollutants, and achieves efficient removal and environmentally friendly water treatment effects.

CN117323842BActive Publication Date: 2025-03-25CHINA UNIV OF GEOSCIENCES (BEIJING)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311543769.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-20
Publication Date
2025-03-25
Estimated Expiration
2043-11-20

AI Technical Summary

Technical Problem

The existing water treatment membrane technology has low efficiency and may lead to secondary pollution in the removal of difficult-to-degrade pollutants, and the activation efficiency and free radical utilization rate of advanced oxidation technology are relatively low.

Method used

A two-dimensional layered silicate mineral film loaded with transition metal ions/oxides is formed in combination with advanced oxidation technology to form a composite film coupled with advanced oxidation technology for the removal of difficult-to-degrade pollutants in wastewater.

Benefits of technology

It has achieved efficient removal of difficult-to-degrade pollutants, improved the activation efficiency and utilization rate of free radicals, reduced the risk of environmental secondary pollution, and showed good circulation stability and degradation efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117323842B_ABST
    Figure CN117323842B_ABST
Patent Text Reader

Abstract

The present invention provides a preparation and application of a mineral functional membrane coupled with an advanced oxidation technology, wherein a mineral material loaded with transition metals is stripped into a nanosheet layer with a large diameter-to-thickness ratio by a chemical-mechanical method, and then filtered into a membrane using a vacuum filtration device, and then persulfate and wastewater containing difficult-to-degrade organic pollutants are mixed and filtered through a transition metal-based mineral membrane with a (sub) nanopore structure, and wastewater treatment is finally completed. The mineral material selected by the present invention has a large ion exchange capacity, can provide sufficient adsorption sites for transition metals, and has (sub) nanometer-scale channels, producing a confined catalytic effect, so that the channels become nanoreactors of advanced oxidation technology. In the wastewater treatment process, adsorption and degradation are achieved simultaneously, and the removal efficiency of organic pollutants is finally effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment membranes, and in particular relates to the preparation and application of a mineral functional membrane coupled with an advanced oxidation technology. Background Art

[0002] The rapid development of the global economy and the acceleration of urbanization have caused serious water pollution, further exacerbating the depletion of freshwater resources. Difficult-to-degrade pollutants continue to remain, accumulate and migrate in the water, causing the water quality to continue to deteriorate, which has a great impact on human health and social sustainable development. Therefore, efficient and deep treatment of wastewater is one of the keys to solving the problem of water pollution.

[0003] Membrane separation technology has the advantages of simple process, low energy consumption, no secondary pollution and good separation effect. It is recognized as an efficient water treatment technology for effectively removing micropollutants. However, its large-scale application is still restricted by permeability, selectivity, stability and energy consumption. In addition, the difficult-to-degrade pollutants in the retained concentrate may be released into the surrounding environment, causing secondary pollution. In recent years, advanced oxidation process technologies (AOPs) for water treatment have attracted widespread attention because they can efficiently generate reactive oxygen species (ROS) that can effectively attack and degrade target pollutants. These ROS include sulfate radicals (SO 4 ·– ), hydroxyl radicals ( · OH), singlet oxygen ( 1 O 2 ) and superoxide radicals ( · O 2 – ) etc. However, due to the limited mass transfer of this technology and · OH (<1ms) and SO 4 ·– (30-40ms) Its lifespan in water is extremely short, which results in its application in water pollution control being limited by low activation efficiency and low free radical utilization.

[0004] China has a vast territory and abundant resources, and has rich and inexpensive mineral reserves. Taking the mineral montmorillonite as an example, two-dimensional montmorillonite is a 2:1 type layered silicate mineral, and each wafer layer is composed of two layers of silicon-oxygen tetrahedrons and one layer of aluminum-oxygen octahedrons. Due to the lattice substitution effect, the structural unit layer of montmorillonite has a natural negative charge and can adsorb ions such as sodium, potassium, magnesium, and calcium, so montmorillonite has ion exchangeability. The exfoliated montmorillonite is a two-dimensional nanosheet with a large aspect ratio, a diameter of about 100-200nm, a single layer thickness of about 1nm, with strong electronegativity, minimal steric hindrance, and the best expansion, which can be used as a kinetically independent sheet particle. The two-dimensional nanosheets are stacked in an orderly manner to form a membrane material with an excellent pore structure. When the pores reach the (sub) nanometer scale, a confinement effect will occur. Therefore, by loading transition metal ions / oxides on the two-dimensional nanosheets to prepare membrane materials with (sub) nanometer-scale pores, nanoreactors are provided for advanced oxidation technology.

[0005] The inventor's previous patent CN202311391827.5 discloses a composite membrane for heavy metal pollution control. It is a composite membrane obtained by organic modification and inorganic modification of a dispersion of a two-dimensional layered silicate mineral after vacuum filtration to form a film. The reduction ability of Fe(II) and the adsorption effect of the two-dimensional membrane of silicate minerals have a good removal effect on heavy metal ions in water. However, it is powerless against organic matter in water, especially organic macromolecules, such as dye molecules. Moreover, due to the narrow pores of the two-dimensional membrane of layered silicate minerals, after adsorbing organic macromolecules whose size is much larger than that of water molecules, it is easy to cause blockage, which greatly reduces the treatment efficiency. Therefore, it is also necessary to develop a type of composite membrane that can effectively treat organic pollutants in water. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a preparation and application of a mineral functional membrane coupled with an advanced oxidation technology. By loading transition metal ions and / or transition metal oxides that have an activation effect on persulfate and combining with persulfate, the refractory pollutants in wastewater can be effectively removed and can be used for a long time.

[0007] To achieve the above object, the present invention adopts the following specific technical solutions:

[0008] A mineral functional membrane coupled with advanced oxidation technology comprises a base membrane and a two-dimensional layered silicate mineral membrane. The two-dimensional layered silicate mineral membrane is attached to the surface of the base membrane and loaded with active sites capable of activating persulfate.

[0009] Furthermore, the base membrane has a thickness of 10-20 μm and a pore size of 0.1-1 μm, preferably 0.3-0.5 μm; the base membrane material is a filter membrane material selected from nylon or PTFE; and the modified two-dimensional layered silicate mineral membrane has a thickness of 5-20 μm.

[0010] Furthermore, the two-dimensional layered silicate mineral is selected from at least one of montmorillonite, vermiculite and mica; and the active sites capable of activating persulfate are ions of transition metal M and / or oxides of transition metal M.

[0011] Furthermore, the transition metal M is selected from Co, Fe, Mn, V, and Ag.

[0012] The present invention provides a method for preparing the composite membrane coupled with the advanced oxidation technology, comprising the following steps:

[0013] 1) mixing a transition metal M source and a two-dimensional layered silicate mineral powder and calcining the mixture to obtain a precursor;

[0014] 2) dispersing the precursor powder in water to obtain a precursor dispersion;

[0015] 3) mixing the precursor dispersion with an aqueous solution of a quaternary ammonium salt, heating and stirring at a constant temperature, then naturally cooling to room temperature, centrifuging, washing, and drying to obtain transition metal-modified mineral nanosheets, dispersing the mixture in a solvent to obtain a transition metal-modified mineral nanosheet dispersion for standby use;

[0016] 4) At room temperature, pour the dispersion obtained in step 3) into a filtration device covered with a substrate membrane, and vacuum filter until there is no residual liquid in the filter cup, forming a modified two-dimensional layered silicate mineral film on the surface of the substrate membrane to obtain a composite membrane coupled with advanced oxidation technology.

[0017] Furthermore, in step 1), the transition metal M source is selected from at least one of sulfates, nitrates, halides, and their hydrates, such as cobalt sulfate heptahydrate and cobalt nitrate hexahydrate; the mass ratio of the transition metal M source to the two-dimensional layered silicate mineral powder is 1-2:4-7; preferably 1.5:4-7; the calcination temperature is 200-300°C, and the calcination time is 4-10h.

[0018] Furthermore, in step 2), the liquid-to-solid ratio of the precursor to water is 1 g: 100-150 mL; the dispersion is treated under ultrasonic conditions for 30-60 min, and then stirred at room temperature for 20-30 h; the ultrasonic frequency is 60-100 kHz, and the ultrasonic time is 30-60 min.

[0019] Furthermore, in step 3), the quaternary ammonium salt is a long-chain alkyl quaternary ammonium salt, specifically selected from at least one of dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, and hexadecyltrimethylammonium bromide; the mass concentration of the quaternary ammonium salt in the quaternary ammonium salt alcohol solution is 1-3wt%; the amount of the quaternary ammonium salt is 10-20wt% of the mass of the two-dimensional layered silicate mineral powder; the temperature for heating and constant temperature is 70-80°C; the stirring speed is 500-1000rpm, and the stirring time is 2-4h; the solvent is selected from at least one of water, methanol, and ethanol; and the concentration of the modified mineral nanosheet dispersion is 1-5mg / mL.

[0020] Furthermore, in step 4), there is no particular limitation on the vacuum degree of vacuum filtration, as long as it can be evacuated until there is no residual liquid in the filter cup, such as 0.01-0.1 MPa.

[0021] The present invention also provides a method for treating organic pollutants in wastewater, comprising the following steps: adding persulfate into wastewater containing organic pollutants, and passing through the composite membrane of the coupled advanced oxidation technology.

[0022] The present invention prepares a mineral membrane loaded with transition metal ions / oxides and applies it to wastewater containing difficult-to-degrade organic pollutants. Since the mineral material has a large specific surface area and ion exchange capacity, it can load more transition metal ions / oxides for activating persulfate, so that the membrane material has abundant reaction sites. The mineral nanosheets after peeling have a large aspect ratio, and the constructed channels can reach the (sub) nanometer level, thereby producing a confinement effect, making the channels a nanoreactor for advanced oxidation technology. Mineral materials are generally able to adsorb organic pollutants. With the progress of advanced oxidation technology, the adsorption and degradation of organic pollutants on the membrane material can be achieved simultaneously. Based on the above characteristics, the mineral membrane material has the advantages of high degradation efficiency, low cost and good stability.

[0023] Furthermore, the persulfate is selected from at least one of sodium persulfate, potassium persulfate, and ammonium persulfate; and the organic pollutants are pollutants such as pharmaceuticals, personal care products (PPCPs), dyes, and phenols.

[0024] Furthermore, the amount of sulfate added for filtration is 0.1-1g / L, which can be adjusted according to the concentration of organic pollutants in the wastewater. When the organic wastewater passes through the composite membrane coupled with the advanced oxidation technology, it can be pressurized at the front end, or it can be directly added to the filtration device with the composite membrane, and the organic wastewater can be quickly passed through by vacuum filtration, which can significantly enhance the wastewater treatment efficiency.

[0025] Taking Rhodamine B as an example, the composite membrane of the present invention is used to degrade 10 mg / L of Rhodamine B. After 12 hours of continuous degradation of Rhodamine B, the degradation rate is still as high as over 90%. Based on the experimental results, it is concluded that the mineral membrane material has good cyclic stability.

[0026] The present invention uses two-dimensional layered silicate minerals to prepare nanosheets loaded with transition metal ions / oxides, and assembles them into a confined structure membrane with rich (sub) nanopores. Studies have shown that nano-confined space catalysis can not only promote the decomposition of PMS and increase the yield of free radicals, but also greatly shorten the migration distance of free radicals to target pollutants, ensure the effective contact distance between free radicals and pollutants within the half-life, and achieve high-intensity and intensive spatial utilization of free radicals, thereby improving catalytic efficiency. In comparison, when a two-dimensional layered membrane without coupling advanced oxidation technology treats organic pollutants, the solution flux is greatly reduced due to the blockage of organic molecules in the pores, resulting in extremely low treatment efficiency.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The present invention overcomes the disadvantage of membrane filtration technology that membrane pollution can easily cause secondary pollution to the environment by coupling advanced oxidation technology to membrane materials; and overcomes the disadvantages of low activation efficiency and low free radical utilization rate of traditional advanced oxidation technology by coupling advanced oxidation technology with confined catalysis.

[0029] 2. The present invention has experimentally confirmed that the mineral separation membrane material coupled with the advanced oxidation technology has excellent recycling performance and stability. The mineral membrane is used to degrade 10 mg / L of Rhodamine B. After recycling for 5 times, its degradation rate is still as high as over 90%. Rhodamine B is degraded for 12 hours continuously, and its degradation rate is still as high as over 90%.

[0030] 3. The present invention uses low-cost mineral materials and a simple-to-operate vacuum filtration device to prepare the membrane. The obtained membrane material has high degradation ability and degradation efficiency, which greatly reduces the cost of wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a schematic diagram of constructing a composite membrane by vacuum filtration in the present invention;

[0032] Figure 2 is a schematic diagram of the composite membrane obtained in Example 1;

[0033] Figure 3 This is a SEM image of the composite membrane obtained in Example 1 at a size of 10 mm;

[0034] Figure 4This is a SEM image of the composite membrane obtained in Example 1 at a size of 20 mm;

[0035] Figure 5 This is a comparison diagram of Rhodamine B before and after mineral separation membrane treatment in Example 1;

[0036] Figure 6 This is a comparison diagram of methylene blue before and after the mineral separation membrane treatment in Example 1;

[0037] Figure 7 This is a comparison chart of methyl orange before and after mineral separation membrane treatment in Example 1. DETAILED DESCRIPTION

[0038] The present invention is further described below in conjunction with specific examples, but is not limited to the contents of the specification. All reagents used are commercially available reagents in the art.

[0039] Montmorillonite (MMT) was purchased from NANOCOR, USA. Specifications:

[0040] project MMT(Nanocor PGN) color Off-white CEC(meq / 100g)±10% 120 Aspect Ratio 300-500 proportion 2.6 Maximum moisture (%) 12% pH(5% dispersion) 9-10

[0041] Main oxide content of montmorillonite:

[0042] Element <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Na 2 The]]> <![CDATA[Fe 2 THE 3 ]]> MgO <![CDATA[SO 3 ]]> CaO <![CDATA[K 2 The]]> <![CDATA[TiO 2 ]]> <![CDATA[P 2 THE 5 ]]> content 64.38 23.36 3.91 3.58 2.71 0.837 0.657 0.275 0.148 0.0483

[0043] Example 1

[0044] 1) 1.5 g of cobalt sulfate heptahydrate and 4 g of montmorillonite were mixed and calcined in a muffle furnace at a temperature of 200° C. for 10 h to obtain a cobalt-based montmorillonite precursor;

[0045] 2) 0.4 g of cobalt-based montmorillonite precursor was dissolved in 50 ml of deionized water for ultrasonic dispersion treatment at an ultrasonic dispersion power of 80 kHz and an ultrasonic time of 30 min, and then stirred at room temperature for 24 h to obtain a precursor dispersion;

[0046] 3) adding 4 g of 1 wt% hexadecyltrimethylammonium bromide aqueous solution to the precursor dispersion obtained in step 2), heating to 70° C. and stirring at a constant temperature of 500 rpm for 2 h, then naturally cooling to room temperature, centrifuging, washing with deionized water 3 times, drying, and dispersing into an ethanol solution to obtain a modified cobalt-based montmorillonite nanosheet dispersion with a concentration of 5 mg / mL for standby use;

[0047] 4) At room temperature, the dispersion obtained in step 3) was poured into a filtration device covered with a PTFE substrate membrane with a pore size of 0.45 mm and a thickness of 20 μm. The vacuum degree was 0.10 MPa, and vacuum filtration was performed until there was no residual liquid in the filter cup. The amount of dispersion was controlled so that the thickness of the modified montmorillonite two-dimensional membrane was 5 μm and the radius was 1 cm, that is, the area of ​​the membrane was about 3.14 cm2 , a composite membrane coupled with advanced oxidation technology is obtained.

[0048] Figure 1 The present invention is a schematic diagram of constructing a two-dimensional channel of montmorillonite by vacuum filtration, specifically, a composite membrane is obtained by vacuum filtration through a filtration device. The present invention does not require complex equipment, and only requires a vacuum filtration device such as a conventional laboratory filtration device to complete the construction of the two-dimensional channel of montmorillonite. If it is necessary to scale up production, it only needs to use suitable industrial vacuum filtration equipment, such as a belt vacuum filter.

[0049] Figure 2 This is a photograph of the composite film obtained in Example 1.

[0050] Figure 3 This is the SEM image of the composite membrane obtained in Example 1 at a size of 10 mm.

[0051] Figure 4 This is the SEM image of the composite membrane obtained in Example 1 at a size of 20 mm.

[0052] As can be seen from the SEM image, the prepared composite membrane is a two-dimensional structure stacked layer by layer, with a large number of two-dimensional (sub) nanopores inside. The rich (sub) nanoscale pore flux can not only fully expose the catalytic active sites, but also limit the catalytic reaction to the (sub) nanoscale space, reduce the mass transfer distance from ROS to pollutants, and enable the generated ROS to quickly contact and degrade pollutants, achieving efficient degradation performance.

[0053] 5) 10 mL of 10 mg / L rhodamine B was mixed with 4 mg of persulfate and poured onto the composite membrane on the filtration device in step 4), and vacuum filtered at a vacuum degree of 0.10 MPa until there was no residual liquid in the filter cup.

[0054] Figure 5 This is a comparison of the Rhodamine B aqueous solution before and after the composite membrane treatment in Example 1. After the aqueous solution containing Rhodamine B is filtered through the rapid filtration device containing the composite membrane, it quickly changes from bright red to a very light color, almost colorless.

[0055] 6) 10 mL of 10 mg / L methylene blue was mixed with 4 mg of sodium persulfate and poured onto the composite membrane on the filtration device in step 4), and vacuum filtered at a vacuum degree of 0.10 MPa until there was no residual liquid in the filter cup.

[0056] Figure 6 This is a comparison chart of the methylene blue aqueous solution in Example 1 before and after the composite membrane treatment. After suction filtration, the color changes from blue to nearly colorless.

[0057] 7) 10 mL of 10 mg / L methyl orange was mixed with 4 mg of persulfate and poured onto the composite membrane on the filtration device in step 4), and vacuum filtered at a vacuum degree of 0.10 MPa until there was no residual liquid in the filter cup.

[0058] Figure 7 This is a comparison chart of methyl orange before and after composite membrane treatment in Example 1; after filtration, the color changes from orange to nearly colorless.

[0059] It can be seen that, after the composite membrane provided in Example 1 allows wastewater containing different organic dyes to pass through the composite membrane quickly by suction filtration, the color becomes significantly lighter and almost colorless.

[0060] Example 2

[0061] The rest is the same as Example 1, except that in step 1), the amount of montmorillonite is changed to 7 g; and the calcination temperature is changed to 300° C., and the calcination time is changed to 6 h.

[0062] Example 3

[0063] The rest is the same as Example 1, except that in step 1), the amount of montmorillonite is changed to 10 g; and the calcination temperature is changed to 300° C. and the calcination time is changed to 6 h.

[0064] Example 4

[0065] The rest is the same as Example 1, except that in step 1), the amount of montmorillonite is changed to 3 g; and the calcination temperature is changed to 300° C., and the calcination time is changed to 6 h.

[0066] Example 5

[0067] The rest is the same as Example 1, except that in step 3), 4 g of 1 wt % hexadecyltrimethylammonium bromide aqueous solution is replaced by 1.5 g of 3 wt % dodecyltrimethylammonium bromide aqueous solution.

[0068] Example 6

[0069] The rest is the same as Example 1, except that in step 4), the amount of the dispersion liquid is controlled so that the thickness of the modified montmorillonite two-dimensional film is 10 μm.

[0070] Example 7

[0071] The rest is the same as Example 1, except that in step 1), 1.5 g of cobalt sulfate heptahydrate is replaced by 1.5 g of ferrous sulfate heptahydrate.

[0072] Comparative Example 1

[0073] The rest is the same as Example 1, except that in step 1), cobalt sulfate heptahydrate is not added.

[0074] Comparative Example 2

[0075] The rest is the same as Example 1, except that in step 3), the quaternary ammonium salt is not modified, and ethanol is directly used to prepare a 5 mg / mL cobalt-based montmorillonite nanosheet dispersion.

[0076] Comparative Example 3

[0077] Mix 10ml of 10mg / L rhodamine B and 4mg of sodium persulfate and pour into the filter cup, add 1.5mg of cobalt sulfate heptahydrate, and perform vacuum filtration at a vacuum degree of 0.10Mpa until there is no residual liquid in the filter cup. 1.5mg of cobalt sulfate heptahydrate is added because a 5μm membrane requires 2ml of 2mg / ml dispersion, so there should be 4mg of cobalt-loaded montmorillonite. According to the ratio of cobalt and MMT, there should be 1.5mg of cobalt sulfate heptahydrate.

[0078] Application Examples

[0079] Taking Example 1 as an example to treat a 10 mg / L Rhodamine B aqueous solution, the above-mentioned examples and comparative examples are compared in terms of their treatment capacity for a 20 min Rhodamine B aqueous solution. After the wastewater treatment is completed, the filtrate is filtered with a 0.22 mm filter membrane, and the filtered solution is mixed with 20 mL of 0.2 mol / L Na 2 S 2 O 3 The solutions were mixed to quench free radicals and prevent continued degradation of pollutants. The absorbance in the filtrate was then measured using an ultraviolet spectrophotometer. The results are shown in Table 1 below:

[0080] Table 1

[0081]

[0082] Comparative Example 1 does not add cobalt sulfate heptahydrate, lacks catalytic active sites, and only removes organic pollutants by the interception effect of membrane, and although the removal rate is not very low, the removal speed is very slow. And there is no organic degradation, which will cause the membrane to be blocked later, and therefore can not be used continuously. Comparative Example 2 does not carry out the modification of quaternary ammonium salt, except that the two-dimensional layered silicate mineral stripping effect is not good, and the membrane is also easy to swell and disintegrate in water and cause not being practically applied. Comparative Example 3 does not carry out the load of two-dimensional membrane, causes the free radical utilization rate to decline, and the organic pollutant degradation rate also declines with, and the system cannot be recycled.

[0083] It can be seen that the composite membrane provided by the present invention is loaded with active sites capable of activating persulfate, i.e., transition metal ions or their oxides, and is modified by quaternary ammonium salts. Its dispersion is subjected to vacuum filtration, and a modified montmorillonite two-dimensional membrane with a certain thickness of loaded activation sites is formed on the vacuum filtration film (base membrane), which can simultaneously adsorb and degrade organic pollutants in organic wastewater. In addition, since it is filtration, it is equivalent to accelerating the speed of wastewater flowing through the composite membrane, and can complete the purification of organic wastewater at an ultra-fast speed. Compared with the two-dimensional layered membrane without coupling advanced oxidation, the rate of treating organic pollutants is increased by 10 3 times (using a catalytic membrane to filter 1 ml takes about 2 seconds, and using a membrane without advanced oxidation to process 1 ml takes about 40 minutes, so the time calculation yields 10 3 In addition, the composite membrane is easy to manufacture and apply on a large scale due to its low material cost and simple preparation process.

Claims

1. A mineral functional membrane coupled with advanced oxidation technology, characterized in that: It comprises a basement membrane and a two-dimensional layered silicate mineral membrane, wherein the two-dimensional layered silicate mineral membrane is attached to the surface of the basement membrane, and the two-dimensional layered silicate mineral membrane carries active sites capable of activating persulfate; The mineral functional membrane coupled with the advanced oxidation technology is a two-dimensional structure stacked layer by layer, and has two-dimensional nanopores inside; The basement membrane has a thickness of 10-20 μm and a pore size of 0.1-1 μm; the basement membrane material is a filter membrane material selected from nylon or PTFE; The two-dimensional layered silicate mineral is montmorillonite; The method for preparing the mineral functional membrane coupled with the advanced oxidation technology comprises the following steps: 1) mixing a transition metal M source and a two-dimensional layered silicate mineral powder and calcining the mixture to obtain a precursor; 2) dispersing the precursor powder in water to obtain a precursor dispersion; 3) mixing the precursor dispersion with an aqueous solution of a quaternary ammonium salt, heating and stirring at a constant temperature, then naturally cooling to room temperature, centrifuging, washing, and drying to obtain transition metal-modified mineral nanosheets, dispersing the mixture in a solvent to obtain a transition metal-modified mineral nanosheet dispersion for standby use; the quaternary ammonium salt is at least one selected from dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, and hexadecyltrimethylammonium bromide; 4) At room temperature, pour the dispersion obtained in step 3) into a filtration device covered with a base membrane, and vacuum filter until there is no residual liquid in the filter cup, thereby forming a modified two-dimensional layered silicate mineral film on the surface of the base membrane to obtain a mineral functional membrane coupled with advanced oxidation technology; the thickness of the modified two-dimensional layered silicate mineral film is 5-20 μm.

2. The mineral functional membrane coupled with advanced oxidation technology according to claim 1, characterized in that: The pore size of the basement membrane is 0.3-0.5 μm.

3. The mineral functional membrane coupled with advanced oxidation technology according to claim 1, characterized in that: The active sites capable of activating persulfate are ions of transition metal M and / or oxides of transition metal M.

4. The mineral functional membrane coupled with advanced oxidation technology according to claim 3, characterized in that: The transition metal M is selected from Co, Fe, Mn, V, Ag.

5. The mineral functional membrane coupled with advanced oxidation technology according to claim 1, characterized in that: In step 1), the transition metal M source is selected from at least one of sulfates, nitrates, halides, and hydrates thereof; the mass ratio of the transition metal M source to the two-dimensional layered silicate mineral powder is 1-2:4-7; the calcination temperature is 200-300°C, and the calcination time is 4-10h.

6. The mineral functional membrane coupled with advanced oxidation technology according to claim 5, characterized in that: The transition metal M source is selected from cobalt sulfate heptahydrate and cobalt nitrate hexahydrate; the mass ratio of the transition metal M source to the two-dimensional layered silicate mineral powder is 1.5:4-7.

7. The mineral functional membrane coupled with advanced oxidation technology according to claim 1, characterized in that: In step 2), the liquid-to-solid ratio of the precursor to water is 1 g: 100-150 mL; the dispersion is treated under ultrasonic conditions for 30-60 min, and then stirred at room temperature for 20-30 h; the ultrasonic frequency is 60-100 kHz, and the ultrasonic time is 30-60 min.

8. The mineral functional membrane coupled with advanced oxidation technology according to claim 1, characterized in that: In step 3), the mass concentration of the quaternary ammonium salt in the quaternary ammonium salt alcohol solution is 1-3wt%; the amount of the quaternary ammonium salt used is 10-20wt% of the mass of the two-dimensional layered silicate mineral powder; the temperature for heating and constant temperature is 70-80°C; the stirring speed is 500-1000rpm, and the stirring time is 2-4h; the solvent is selected from at least one of water, methanol, and ethanol; and the concentration of the modified mineral nanosheet dispersion is 1-5mg / mL.

9. The mineral functional membrane coupled with advanced oxidation technology according to claim 1, characterized in that: In step 4), the vacuum degree of vacuum filtration is 0.01-0.1 MPa.

10. A method for treating organic pollutants in wastewater, comprising the following steps: Persulfate is added to wastewater containing organic pollutants and passed through a mineral functional membrane coupled with an advanced oxidation technology as described in any one of claims 1-9.

11. The method according to claim 10, characterized in that The persulfate is selected from at least one of sodium persulfate, potassium persulfate and ammonium persulfate; the organic pollutants are medicines, personal care products, dyes and phenolic pollutants.

12. The method according to claim 11, characterized in that The amount of persulfate added is 0.1-1 g / L.

Citation Information

Patent Citations

  • Composite membrane for heavy metal pollution treatment and preparation method thereof

    CN117181008A

  • Method for in-situ remediation of dioxin-polluted soil based on modified zero-valent iron

    CN115178583A

  • Monatomic catalytic membrane for persulfate wastewater treatment system as well as preparation and application of monatomic catalytic membrane

    CN115869980A